Development and Validation of Hplc Method For Analysis of Paclitaxel Drug - Phadtare, Manoj; Aher, Smita; Bachhav, R.S.; Phadatre, Dipti G.; Patil, Anita (Journal of Neonatal Surgery, 2025)
A high-performance liquid chromatography method was established for the quantification of related components in an intravenous emulsion containing a paclitaxel–cholesterol combination. The separation was accomplished via an Agilent Luna® 100 A° C8 (150 X 4.6 mm, 5 µm), maintained at 20C°. The gradient mobile phase comprised acetonitrile and water, with a flow rate of 1.2 ml/min. The ultraviolet detection wavelength was established at 230 nm. The sample solution preparation commenced with the incorporation of anhydrous sodium sulphate to disrupt the emulsion. Methanol and ethyl ether were subsequently introduced to extract the medication and eliminate the emulsion's components using extraction and centrifugation. The method demonstrated selectivity, sensitivity, robustness, linearity, repeatability, accuracy, and appropriateness for quantifying paclitaxel-related substances in emulsion formulations, with the primary degradation products.